Addition of Azolla Microphylla oo Feed on The Digestive Tract of Magelang Ducks - Faishal Rizqy Setyawan; Yosephine Laura Raynardia Esti Nugrahini; Danes Suhendra; Syaiful Iqbal (Animal Husbandry Study Program, Faculty of Agriculture, Timor University, 2022)
This study aims to determine the effect of additional feeding Azolla microphylla on the digestive tract of Magelang ducks. This research was conducted for 7 weeks in the experimental cage of Tidar University. The experiment was conducted using a completely randomized design with 4 treatments P0 (0% Azolla microphylla), P1 (10% Azolla microphylla), P2 (15% Azolla microphylla) P3 (20% Azolla microphylla) with 5 replications. The livestock used were 40 male Magelang ducks. The parameters observed were the length and weight of the digestive tract of Magelang Ducks. Data were analyzed using a completely randomized design (CRD) then continued with Duncan's test. Analysis of variance showed that supplementary feeding Azolla microphylla had no significant effect (on the percentage of crop length, jejunum, caecum, large intestine, cloaca, liver and esophageal weight, crop, proventiculus, gizzard, duodenum, jejunum, caecum, cloaca, and liver, but had a significant effect on the percentage of length of the esophagus, proventriculus, gizzard, duodenum, ileum, and percentage of weight of the ileum, and colon.